Forecasting of consumer demand with the use of multi-factor dynamic models - Liliya F. Garifova, Ekaterina A. Grigoreva, Elvira A. Polovkina, (Opción, 2019)
In this paper, it is proposed to use a multifactor nonlinear dynamic model to predict consumer demand. For this purpose, a method of varying differences is proposed in order to reduce the autocorrelation of time series. According to the multifactor dynamic model of consumer demand, the authors have proposed a model for forecasting the demand for goods depending on the given values of the total turnover, price indices and the influence of other factors on the formation of consumer demand of the population. The character of dependencies and nonlinear trends was studied, what has allowed qualitative models to obtain.